2022
DOI: 10.1007/s10802-022-00920-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Affective, and Cognitive Parenting Mechanisms of Child Internalizing and Externalizing Problems during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led to increased mental health concerns, including depression and anxiety among parents and internalizing and externalizing problems among youth. To better understand the mechanisms and moderators of child mental health during the pandemic, the current study tested two moderated mediation models in which parent depression and anxiety indirectly impacted child internalizing and externalizing problems through negative effects on multiple parenting variables, with these associations mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Here, we point out that, in this study, we did not collect direct data on parents and teacher health and on illnesses suffered in the pandemic period, but recent international research has reported a negative impact of this emergency also on these populations (Fosco et al, 2022; Roos et al, 2021; Russell et al, 2020). Penner et al (2022) found a positive association between COVID‐19 stressors and parental depression/anxiety symptoms: this combination of high COVID‐19 stressors and greater depression/anxiety in parents may have led to a greater frequency of negative parenting (poor supervision, hostility). International literature includes research that shows how the COVID‐19 pandemic also impacted teachers' mental health (Lizana & Lera, 2022), especially those who already had physical and mental health problems prepandemic, higher levels of negative affect and worry and poor life satisfaction, and resilience (Lacomba‐Trejo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we point out that, in this study, we did not collect direct data on parents and teacher health and on illnesses suffered in the pandemic period, but recent international research has reported a negative impact of this emergency also on these populations (Fosco et al, 2022; Roos et al, 2021; Russell et al, 2020). Penner et al (2022) found a positive association between COVID‐19 stressors and parental depression/anxiety symptoms: this combination of high COVID‐19 stressors and greater depression/anxiety in parents may have led to a greater frequency of negative parenting (poor supervision, hostility). International literature includes research that shows how the COVID‐19 pandemic also impacted teachers' mental health (Lizana & Lera, 2022), especially those who already had physical and mental health problems prepandemic, higher levels of negative affect and worry and poor life satisfaction, and resilience (Lacomba‐Trejo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we point out that, in this study, we did not collect direct data on parents and teacher health and on illnesses suffered in the pandemic period, but recent international research has reported a negative impact of this emergency also on these populations (Fosco et al, 2022;Roos et al, 2021;Russell et al, 2020). Penner et al (2022) found a positive association between COVID-19 stressors and parental depression/anxiety symptoms: this combination of high COVID-19 stressors and greater depression/ anxiety in parents may have led to a greater frequency of negative parenting (poor supervision, hostility).…”
Section: Limitation Future Directions Of the Study And Practical Impl...mentioning
confidence: 96%
“…Most of them were quantitative and collected data during the first 7 months of 2020 (Liang et al, 2020;Morelli et al, 2020Morelli et al, , 2022Petrocchi et al, 2020;Andrés-Romero et al, 2021;Bate et al, 2021;Cellini et al, 2021;Li and Zhou, 2021;Liu et al, 2021Liu et al, , 2022Mariani Wigley et al, 2021;Wang et al, 2021a,b,c;Dodd et al, 2022;Lionetti et al, 2022;Martiny et al, 2022;Oliveira et al, 2022;Ravens-Sieberer et al, 2022), as did the qualitative studies (Idoiaga et al, 2020;Cortés-García et al, 2021). One quantitative study (Penner et al, 2022) collected data during the first months of 2021 (February-April) Most of the papers applied a cross-sectional quantitative study design (n = 27); three collected longitudinal quantitative data. All three qualitative studies were cross-sectional.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Of 2207 individuals who consented, 1411 were excluded based on exclusion criteria, resulting in 796 in the final sample. See Penner et al, 2022 for more details on recruitment.…”
Section: Participants and Proceduresmentioning
confidence: 99%